2022
DOI: 10.3390/ijms23136961
|View full text |Cite
|
Sign up to set email alerts
|

Lmx1a-Dependent Activation of miR-204/211 Controls the Timing of Nurr1-Mediated Dopaminergic Differentiation

Abstract: The development of midbrain dopaminergic (DA) neurons requires a fine temporal and spatial regulation of a very specific gene expression program. Here, we report that during mouse brain development, the microRNA (miR-) 204/211 is present at a high level in a subset of DA precursors expressing the transcription factor Lmx1a, an early determinant for DA-commitment, but not in more mature neurons expressing Th or Pitx3. By combining different in vitro model systems of DA differentiation, we show that the levels o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 83 publications
(133 reference statements)
0
7
0
Order By: Relevance
“…Recent research has demonstrated the importance of the Lmx1a-miR-204/211-Nurr1 axis in the differentiation of mDA neurons [58]. Additionally, mice that are overexpressed with mutant alpha-synuclein and simultaneously lacking one Nurr1 allele showed the enhanced age-dependent reduction of Nurr1 protein levels, a decreased number of mDA neurons, as well as increased neuroinflammation and alpha-synuclein aggregation [59].…”
Section: Pitx3 and Nurr1mentioning
confidence: 99%
“…Recent research has demonstrated the importance of the Lmx1a-miR-204/211-Nurr1 axis in the differentiation of mDA neurons [58]. Additionally, mice that are overexpressed with mutant alpha-synuclein and simultaneously lacking one Nurr1 allele showed the enhanced age-dependent reduction of Nurr1 protein levels, a decreased number of mDA neurons, as well as increased neuroinflammation and alpha-synuclein aggregation [59].…”
Section: Pitx3 and Nurr1mentioning
confidence: 99%
“…The miR-218-1 À/À and miR-218-2 À/À (referred to as KO1 and KO2, respectively) were generated by using CRISPR/Cas9 dual-nickase mediated nonhomologous end joining following a previously published protocol (Ran et al, 2013). Briefly, two pairs of single guide RNA (sgRNA) targeting the miR-218-1 and the miR-218-2 genomic loci at both bottom and top strands were designed using the CRISPR double nickase design tool from the Feng Zang laboratory (https://www.zlab.bio/resources) and evaluated for their low off-target activity.…”
Section: Generation Of Mouse Mutant Strainsmentioning
confidence: 99%
“…Cas9n mRNA and sgRNA templates were amplified with T7 promoter sequence-conjugated primers and transcribed in vitro with mMESSAGE mMACHINE T7 Ultra Kit (Invitrogen) and MEGAshortscript T7 Kit (Invitrogen), respectively. The in vitro RNAs were injected into pronuclear stage fertilized mouse eggs, which were then transferred into the oviduct of pseudo-pregnant female mice (C57/Bl) (Ran et al, 2013). F1-mice carrying indels were mated with WT animals and subsequently Sangersequencing was performed on homozygotes DNA.…”
Section: Generation Of Mouse Mutant Strainsmentioning
confidence: 99%
See 2 more Smart Citations